Peranan Face Reading dalam Kitab Primbon "Betaljemur Adammakna" terhadap Konseling Pra-Nikah (Jurnal Bimbingan dan Konseling Islam, 2022)
This article aims to explain how the life cycle of a marriage, starts from the guidelines for choosing a potential partner through face reading or panyandra firasating manungsa in the primbon book "Betaljemur Adammlasi-BA," along with its role in prospective ta'aruf partners. Betaljemur Adammlasi is a primbon book by Kangjeng Pangeran Harya (KPH) Tjakraningrat, when he was still active in the Ngayogyakarta Hadiningrat Sultanate, Yogyakarta. This book emerged as a result of the assimilation and acculturation of stories from Islamic treasures, namely the story of Amir Hamzah which in Javanese tradition is called Wong Agung Menak. In the BA primbon book, several aspects of gut science/physiognomy are found in reading people's faces, from the head, hair, forehead/forehead, eyebrows, ears, eyes, nose, mouth, lips, cheeks, teeth, and chin. Face reading or panyandra sifating manungsa in the BA primbon book is an assimilation of culture, local wisdom, and is supported by religious values, resulting in the knowledge of titen. Furthermore, it can play a role for prospective ta'aruf pairs as preventive and curative materials.